Colorectal Screening Program in Northern Portugal: First Findings - Monteiro, Hugo (2022)
Introduction: In Portugal, a colorectal cancer screening program based on faecal immunochemical test followed by colonoscopy was shown to be cost-effective for individuals between 50 and 74 years old. We report the first findings of the implementation of a population-based program In Northern Portugal.Material and Methods: In the pilot phase, eligible subjects were allocated either to a direct mailing invitation or to primary care centers. In the first year of program implementation, we assessed the uptake rate, the faecal immunochemical test -positivity rate, the diagnostic yield of advanced neoplasia, and the quality parameters for post-faecal immunochemical test + colonoscopy.Results: We invited 100 501 eligible subjects (49% male with a median age of 55 years). Of these, 5228 participated in the pilot phase and 95 273 participated in the first year of the program. In the first year of the program, the adherence was 29%, with a positivity rate of 5% and a 60% compliance to colonoscopy. The faecal immunochemical test-detection rate of advanced neoplasia was 0.35/1000 subjects, and the positive predictive value at post- faecal immunochemical test + colonoscopy was 44% and 2% for advanced adenoma and invasive cancer, respectively. No major adverse events were reported after colonoscopy.Discussion: The suboptimal adherence to faecal immunochemical test and post-faecal immunochemical test + colonoscopy remains the most urgent step to be addressed.Conclusion: A centralized invitation system based on direct mailing was feasible and both colonoscopy quality and diagnostic yield were adequate antecipating the success of the programme.